Asphaltene/polymer composites: Morphology, compatibility, and rheological properties. (30th August 2022) - Eshraghian, Afrooz; Kamkar, Milad; Sundararaj, Uttandaraman
Abstract: In this study, we investigate the use of asphaltene, a natural waste product that is inevitably formed during heavy oil processing, as a filler in polymer composites. The focus of this work is on the compatibility of various asphaltenes, featuring different polarities, with several polymers, including polypropylene (PP), polystyrene (PS), polymethyl methacrylate (PMMA), and polycarbonate (PC). The Hansen solubility parameters were plotted to predict the compatibility of polymers with different asphaltenes. Then, polymer composites were prepared by two common techniques: melt mixing and solution mixing. The dispersion state of the asphaltenes in each polymer was investigated by using imaging and rheological techniques. This work showed that the network structure of the asphaltenes and, thus, the final properties of the composites can be controlled by the polarity of asphaltenes, mixing technique, and melt viscosity of the polymer. For instance, more polar asphaltene (Asph P) produced smaller aggregates in PMMA, which has a higher polar solubility parameter than PP or PS. At 2.5 wt.% of asphaltene, Asph P showed 26% and 177% larger asphaltene agglomerates in PP and PS, respectively, than the less polar asphaltene (Asph Al). PS/asphaltene and PMMA/asphaltene composites prepared by the solution mixing method exhibited better dispersion compared to their melt‐mixed counterparts. In melt‐mixed composites, the dispersion quality of the asphaltene was better for polymers with higher melt viscosity. Thus, a careful choice of polymer, asphaltene, and preparation conditions can be used to tune the properties of asphaltene/polymer composites. Abstract : Effect of affinity of asphaltene and polymer and polymer melt viscosity on asphaltene dispersion.